Long-term clinical outcomes of isolated orbital floor fracture reconstruction using nonresorbable implants - Ayman E Abd El Ghafar; Nashaat Shawky; Mahrous Hassan Shaheen; Khalid Abdel Aziz; Mostafa Mohamed Diab (Indian Journal of Ophthalmology)
Purpose: There are no universally established guidelines for material selection in orbital wall fracture reconstruction. With an increasing preference for permanent implants, this study aimed to compare the long-term clinical outcomes of three different non-resorbable materials in reconstructing isolated orbital floor fractures. Design: A retrospective, interventional comparative study. Methods: The medical records of patients with unilateral pure orbital floor fractures who underwent orbital reconstruction using non-resorbable alloplastic implants at two tertiary referral centers between January 2017 to December 2021 were reviewed. Cases with non-pure orbital floor blowout fractures and/or <2 years of follow-up were excluded. Patients were separated into three groups according to the implant material type: porous polyethylene (PPE) sheet, polypropylene (PP) mesh, and titanium (Ti) mesh. These groups were then retrospectively analyzed for clinical outcomes, implant-related complications, and patient’s satisfaction. Results: Sixty-six patients met the inclusion criteria. Twenty-four patients (36.36%) received PPE sheets, 20 patients (30.3%) had PP mesh, and 22 patients (33.33%) received Ti mesh. At the 6-month postoperative visit, nine patients (40.9%) in the Ti mesh group experienced postoperative diplopia compared to six patients (30.0%) in the PP group and one patient (4.2%) in the PPE group (P < 0.047). Following the initial 6-month postoperative period, the PP group had more frequent postoperative enophthalmos compared to the other 2 groups. The total ocular motility restriction score was significantly lower in the Ti mesh group compared to the other 2 groups at all follow-up visits. Patient’s satisfaction was significantly higher in the PPE group (median = 10, IQR = 1) compared to the PP (median = 8.5, IQR = 3) and Ti groups (median = 8, IQR = 3), P < 0.001. Reoperation was needed in seven patients (31.8%) in the Ti group, two patients (10%) in the PP group, and none in the PPE group. Conclusions: The use of PPE orbital implants for the repair of isolated orbital floor fracture provides better long-term clinical outcomes compared to PP or Ti mesh and reduces the need for reoperation across all fracture sizes. Ti mesh has been associated with a higher frequency of unfavorable clinical outcomes and implant removal.